Rash and hepatitis within days of starting a new antiretroviral regimen: nevirapine hypersensitivity, secondary syphilis or both?. (March 2014) - Saxon, Cara J; Helbert, Matthew R; Komolafe, Adeniyi J; Higgins, Stephen P
We report a case in which an HIV-positive man developed general malaise, skin rash and biochemical hepatitis within days of starting a nevirapine-based antiretroviral treatment regimen. At the same time, his syphilis serology proved positive. We discuss the diagnostic dilemma: was this a nevirapine hypersensitivity reaction, secondary syphilis or both?